Modeling Fragile X Syndrome in Drosophila - Drozd, Małgorzata; Bardoni, Barbara; Capovilla, Maria (Frontiers in Molecular Neuroscience, 2018)
Intellectual disability (ID) and autism are hallmarks of Fragile X Syndrome (FXS), a hereditary neurodevelopmental disorder. The gene responsible for FXS is Fragile X Mental Retardation gene 1 (FMR1) encoding the Fragile X Mental Retardation Protein (FMRP), an RNA-binding protein involved in RNA metabolism and modulating the expression level of many targets. Most cases of FXS are caused by silencing of FMR1 due to CGG expansions in the 5’-UTR of the gene. Humans also carry the FXR1 and FXR2 paralogs of FMR1 while flies have only one FMR1 gene, here called dFMR1, sharing the same level of sequence homology with all three human genes, but functionally most similar to FMR1. This enables a much easier approach for FMR1 genetic studies. Drosophila has been widely used to investigate FMR1 functions at genetic, cellular and molecular levels since dFMR1 mutants have many phenotypes in common with the wide spectrum of FMR1 functions that underlay the disease. In this review, we present very recent Drosophila studies investigating FMRP functions at genetic, cellular, molecular and electrophysiological levels in addition to research on pharmacological treatments in the fly model. These studies have the potential to aid the discovery of pharmacological therapies for FXS.